THE FIGURE OF VASYL STEFANYK THROUGH THE PRISM OF UKRAINIAN PEDAGOGICAL BIOGRAPHICAL STUDIES - Bilavych, Halyna; Blavt, Oksana; Didukh, Iryna (Mountain School of Ukrainian Carpaty, 2021)
May 14, 2021 marked the 150th anniversary of the birth of Vasyl Stefanyk – a classic of Ukrainian literature, public and political figure, one of the iconic figures of cultural and socio-political life of Ukraine. A number of thematic events took place at Vasyl Stefanyk Precarpathian National University. Pedagogical biographical studies are a little-studied and new direction in Ukrainian science. The purpose of the article is to analyze the life and creative heritage of V. Stefanyk through the prism of Ukrainian pedagogical biography. In research the following research methods are used: general scientific (analysis, synthesis, deduction, induction, comparison, classification, generalization), which allow to argue and justify the experience of studying the figure of Vasyl Stefanyk from the standpoint of pedagogical biographical studies; search and bibliographic for systematization of research sources; comparative and descriptive – to characterize the social and educational activities of the writer; special biographical (biographical, biographical reconstruction, etc.) – determine the methods, techniques of studying various aspects of life and work of Vasyl Stefanyk; etc. One aspect of the study of personalistics is the analysis of the writer's educational environment, which led to their formation as a person. The establishing of V. Stefanyk as a writer, public and educational figure was influenced by a number of factors, including the educational environment. In his life we clearly trace certain stages associated with the acquisition of education: primary education, which he received in Rusiv (three-grade public school (1878–1880)) and in Sniatyn (special, is higher primary school) (1880–1883); gymnasium education (Kolomyia State Gymnasium (1883–1890), Drohobych State Gymnasium named after Franz Joseph I (1891–1892)); university studies (medical faculty of Jagiellonian University (1892– 1900)); and lifelong self-education. In 1900, V. Stefanyk left the Jagiellonian University and fully registered as a writer, educator, and public figure.